Smart direction finding for WLAN antenna using the DSP board - Nuru Al Hidayah Mohamed (Universiti Malaysia Perlis, 2008)
Nowadays digital signal processing (DSP) plays an important role in science and engineering because of the widespread use of computers to process, manipulate and store data. This paper describes about the smart direction finding for WLAN antenna using the DSP Board. It describes a microstep driving method of stepper motor and its DSP-based implementation to analyze the received data by using C programming. Both hardware and software were used in this project. A simple receiver antenna which is an Inset Fed Rectangular Patch Antenna is designed to operate in 802.11-b wireless local area network (WLAN) applications which are (2.40–2.48 GHz). The DSP board will control the movement of the receiver antenna to do the rotation to left or right so that the DSP board can detect at which angle the receiver will receive the strongest signal from the transmitter antenna. The VEE will read the signal received by the receiver antenna from the Network Analyzer for each rotation and then store it to the DSP board. After completing the rotation, the DSP board will analyze all the data and automatically control the receiver antenna to move to the angle that gives it the strongest signal (maximum power) in the wireless frequency range.